Crisis, what crisis? Conceptualizing crisis, UK pluri-constitutionalism and Brexit politics. Issue 9 (2nd September 2021) - Wincott, Daniel; Davies, Gregory; Wager, Alan
ABSTRACT: Has Brexit triggered a constitutional crisis? Crisis is one of a family of concepts, including tipping points, catastrophic equilibrium and failure, identifying it as a decisive moment for overcoming contradictions and ambiguities. Across multiple UK levels – the whole state, constituent nations and different legal jurisdictions – even in 'normal times' the constitution has been marked by both a dominant 'Anglo-British imaginary' and territorial ambiguities. Drawn into political debate, these ambiguities became sources of basic constitutional instability during Theresa May's premiership. Although May avoided full-blown constitutional crisis, one may yet come. Equally, she did oversee basic constitutional change, not necessarily in the form of crisis.